Neutron Diffraction Study of Liquid N-Methylformamide Using EPSR Simulation - Cordeiro, João M.M. [UNESP]; Soper, Alan K. (Amer Chemical Soc, 2009)
The structure of N-methylformamide (NMF) in liquid state has been investigated using a combination of neutron diffraction measurements augmented with isotopic substitution and empirical potential structure refinement computer simulations. The reference potential used was optimized previously and consisted of Coulomb and 6-12 Lennard-Jones interactions for the atoms. The results show that the three-dimensional model of the liquid structure constructed at the correct atomic number density is consistent with the diffraction experimental data. The liquid structure is orientated by the hydrogen bonds among the molecules. Each NMF molecule is, on average, hydrogen bonded to two others. The findings indicate that dimers and "linear" trimers are very stable species in the liquid bulk. Because of that, the liquid is strongly structured into a chain-like structure. Neighboring chains are stabilized with respect to each other by weak O center dot center dot center dot H(C) hydrogen bonds. The results are consistent with the known physicochemical properties of the liquid.